Role of ratio-based metrics in cardiology - A. O. Konradi; A. L. Maslyansky; E. P. Kolesova; E. V. Shlyakhto; P. L.M. Kerkhof (Российский кардиологический журнал, 2020)
In cardiovascular studies, two related parameters that determine the same physical variable are often recorded. Interpretation of the calculated indicators presented in the form of ratios and differences is difficult, since they can be associated with several combinations of primary data giving the same value.Aim. To find a way to overcome this limitation and take a more comprehensive approach.Material and methods. We analyzed the data on left ventricular volume and blood pressure (BP) in 275 patients (women — 207), obtained using echocardiography and BP monitor. To calculate a lost companion (c) value based on a difference or dimensionless ratio, we applied the Pythagorean theorem. The lost companion isdefined as the hypotenuse in each study area. To calculate the pulse pressure companion (PP), the following formula was used: PP(c)=Ö(SBP2+SBP2). Similar methods were applied to ejection fraction (EF), augmentation pressure (AG) and AG/PP ratio, resulting in the ratio called augmentation index (AIx).Results. 1. Mean blood pressure (MBP) acts as a surrogate for the PP companion (PPc) values (R=0,970, N=257). 2. We have identified correlations between PPc and pulse wave velocity (R=0,397, N=193), and AGc with AIx (75) (R=0,662, N=198). 3. EF has an inverse relationship with the end diastolic volume (EDV) (R=-0,559, N=187), and the ventricular-arterial coupling (VAC) correlates with ESV (r=-0,627, N=180). 4. Comparison of EDV and VACc revealed R of 0,949.Conclusion. Companions calculated from the available data can have significant additional diagnostic value without the need for additional measurements. It is important to note that the combination of traditional ratio-based and suggested companions allows for more accurate data on individual patients.